A importância da fisioterapia gerontológica em um grupo de idosos com doença de Alzheimer - Oliveira, Ana Maria Tabet de (2014)
This research aimed to reflect on the application of a physical therapy protocol, within the Gerontologic approach, applied in an elderly home in SP (n=14), all with mild to moderate Alzheimer s disease, assessing three aspects : functionality, cognition and behavior over a period of six months, at a weekly meeting. Functionality was assessed by the Timed Up and Go (TUG)Test and the Pfeffer Questionnaire ;cognition,with the Mini-Mental State Examination (MMSE) , Verbal Fluency Test (VFT) and Clock Drawing Test (CDT) and behavior, by Geriatric Depression Scale (GDS) and Neuropsychiatric Inventory (NPI)by Cummings . Such tests were applied at the beginning, middle and the end of the process. The group was divided into two subroups, according to the analysis of performance on the TUG test: the ones with lower risk of falls (n=7) and increased risk (n=7), with two variables : position (seated and standing) and mutual cooperation during the exercises (with and without cooperation). Each group received a distinct exercise protocol. At three months they were reversed about variables and protocols. The hypothesis is the beneficial effect in the analyzed aspects.To evaluate the results, it was used the SPSS17.0 software(Statistical Package for Social Sciences), the Friedman test for descriptive analysis and for analysis of the tests performance it was applied the SPAD(Système Portables d Analyse dês Donées).Results:significant difference (p<0,05) in behavior ( GDS ) with improvement of depression as well as trends towards improvements in the tests analysed, in distinct phases. Analysis of performance in tests classified them into three gropus : mixed, good and bad results. Conclusion : Although the short period of intervention, it proved positive for the elderly with A.D.